Enhancing Compressive Strength and Dentin Interaction of Mineral Trioxide Aggregate by Adding SrO and Hydroxyapatite - Leny Yuliatun; Eko Sri Kunarti; Widjijono Widjijono; Nuryono Nuryono (Indonesian Journal of Chemistry, 2022)
In this research, the effect of strontium oxide (SrO) and hydroxyapatite (HA) on the properties of mineral trioxide aggregate (MTA) have been studied. MTA contained 20% SiO2, 60% CaO, and 2% Al2O3. Bi2O3 and SrO have been added with 18% (w/w) total percentage. MTA was prepared with a sol-gel process using a weak base (NH3) as a catalyst and calcined at 1000 °C for 3 h. The effect of HA was investigated by adding various percentages (3, 6, and 9%) on the MTA modified with 5% SrO. The modified MTA (MTA-SrO-HA) products were hydrated using water with the MTA to water weight ratio of 3:1. The results showed that tricalcium silicate (C3S), dicalcium silicate (C2S), Bi2O3, and strontium silicate peaks were detected in the XRD patterns. An increase in the intensity in the infrared spectra of CaO occurred after hybridization with HA. In addition, bonding of Ca-O-Si appeared at 879 and 995 cm−1, indicating the formation of cement. MTA modified with 5% SrO and 6% HA showed similar compressive strength to the commercial MTA (ProRoot brand). Furthermore, MTA-SrO5/HA6 showed a strong interface interaction with dentin adheres without any gaps, indicating a potential dental material for the future.